Importance of thermophoretic particles deposition in ternary hybrid nanofluid with local thermal non-equilibrium conditions: Hamilton–Crosser and Yamada–Ota models - Abbas, Munawar; Khan, Nargis; Hashmi, M.S.; Alotaibi, Hammad; Khan, Husna A.; Rezapour, Shahram; Inc, Mustafa (Case studies in thermal engineering, 2024)
This article exhibits a brief study of magneto ternary hybrid nanofluid flow with thermophoretic particle deposition and porous medium based on the extended version of model, known as the Yamada-Ota and Hamilton Crosser models. Thermophoretic particle deposition, which is important in both aero-solution and electrical engineering, is one of the most fundamental methods for transferring small particles across a heat gradient. This suggested model's goal is to evaluate how well Hamilton-Crosser and Yamada-Ota, two trihybrid nanofluid models, perform. Advanced heat transfer systems, in particular the creation of effective cooling and heating technologies, may benefit from this research. Researchers can develop more efficient heat exchangers, boost thermal management in electronic devices, and increase energy efficiency in industrial processes by better understanding how thermophoretic particles behave in complicated nanofluid systems under various conditions. By using the required similarity variables, the MATLAB solver bvp4c package handles the system of ODEs acquired from the leading PDEs to arrive at the numerical solution. The relevant parameters' effects on the relevant fields have been graphically explained. The results show that when inter-phase heat transfer parameter value grows, thermal profile and rate of heat transfer decrease of liquid phase. With regard to heat and mass transfer effectiveness, the Yamada-Ota model performs better than the Hamilton Crosser trihybrid nanofluid model. [Display omitted]